2009
DOI: 10.1002/ange.200806178
|View full text |Cite
|
Sign up to set email alerts
|

Phosphinoborane and Sulfidoborohydride as Chelating Ligands in Polyhydride Ruthenium Complexes: Agostic σ‐Borane versus Dihydroborate Coordination

Abstract: The chemistry of s-borane complexes remains at an early stage of development by comparison to the analogous sdihydrogen and s-silane families. [1][2][3][4][5] However, since the isolation of the first s-borane metal complex in 1996, [6] important findings dealing with B À H bond activation have been regularly disclosed. [7][8][9] The s-borane complexes are often invoked as intermediates in the formation of the corresponding hydridoboryl complexes and the microscopic reverse reductive elimination. More and more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 40 publications
3
17
0
Order By: Relevance
“…The trigonal planar geometry of both boron and nitrogen atoms and the BÀN distance reflect the expected multiple N sp2 À B sp2 bond character in monomeric aminoboranes owing to the p donation of the nitrogen lone pair into the vacant p atomic orbital on boron. It is worth noting that the BÀN and BÀH distances are very similar to those found in two agostic complexes [Cr{HBN(SiMe 3 ) 2 CH=CHCMe 3 }(CO) 4 ] and [RuH 2 {h 2 -HÀB(NiPr 2 )CH 2 PPh 2 }(PCy 3 ) 2 ] as reported recently by Braunschweig and our group (B À N/B À H: 1.4034(16) /1.257 , [17] and 1.404(9) /1.23 (7) , [18] respectively). All these features are in full agreement with the trapping of H 2 BÀNH 2 , [19] the first formal elementary step of dehydrogenation of ammonia-borane [Eq.…”
supporting
confidence: 88%
“…The trigonal planar geometry of both boron and nitrogen atoms and the BÀN distance reflect the expected multiple N sp2 À B sp2 bond character in monomeric aminoboranes owing to the p donation of the nitrogen lone pair into the vacant p atomic orbital on boron. It is worth noting that the BÀN and BÀH distances are very similar to those found in two agostic complexes [Cr{HBN(SiMe 3 ) 2 CH=CHCMe 3 }(CO) 4 ] and [RuH 2 {h 2 -HÀB(NiPr 2 )CH 2 PPh 2 }(PCy 3 ) 2 ] as reported recently by Braunschweig and our group (B À N/B À H: 1.4034(16) /1.257 , [17] and 1.404(9) /1.23 (7) , [18] respectively). All these features are in full agreement with the trapping of H 2 BÀNH 2 , [19] the first formal elementary step of dehydrogenation of ammonia-borane [Eq.…”
supporting
confidence: 88%
“…Compound 3 a was found to be stable at room temperature and was fully characterized by multinuclear NMR spectroscopy. A doublet at δ =37.5 ppm ( 1 J BH =115 Hz) and a broad singlet at δ =5.52 ppm in the 11 B NMR and 1 H{ 11 B} NMR spectra, respectively, reflect the presence of a B(sp 2 )HN i Pr 2 group in 3 a . The integrity of the cyano group is evidenced by a strong nitrile IR stretching frequency observed at trueν˜ =2219 cm −1 .…”
Section: Figurementioning
confidence: 77%
“…6 The postulated agostic complexes B and/or C ( Figure 3) likely to give 3 by B−C bond cleavage and ligand rearrangement were never detected. 4,5 Calculations indicated that substitution of the two H 2 ligands in 1 by ligand 2 affords complex B in an exoergic transformation with ΔG = −2.5 kcal mol −1 . 12 This complex features an agostic B−H bond that is elongated with respect to the free ligand (1.304 Å, B; 1.208 Å, 2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…4,5 The reaction of 2 with [RuH 2 (η 2 -H 2 ) 2 (PCy 3 ) 2 ] (1) carried out in pentane, at room temperature, for 1 min, led after workup to a brown solid analyzed as an equimolar mixture of complex 3 and PCy 3 (Scheme 1). 3 was found to be unstable in solution at room temperature and had to be stored in the solid state, below −30°C .…”
Section: ■ Results and Discussionmentioning
confidence: 99%